1977
DOI: 10.1084/jem.146.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Dengue viruses and mononuclear phagocytes. I. Infection enhancement by non-neutralizing antibody

Abstract: Cultured mononuclear peripheral blood leukocytes (PBL) from nonimmune human beings and monkeys are nonpermissive to dengue 2 virus (D2V) infection at multiplicities of infection of 0.001-0.1, but become permissive when non-neutralizing dengue antibody is added to medium. D2V infection occurred in PBL prepared from anti-coagulated but not from defibrinated plasma. Infection enhancement was produced by multiple lots of heterotypic anti-dengue raised in several mammalian species. Homotypic anti-dengue neutralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
528
0
8

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(549 citation statements)
references
References 26 publications
13
528
0
8
Order By: Relevance
“…27, 43 The concept of ADE was initially proposed for dengue in 1977 and was supported by epidemiological observations in Cuba. 44,45 Data from Cuba demonstrated that DHF was more frequently observed in those patients who had evidence of previous infection with a different serotype. Recent work has provided further support for the concept of ADE.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 99%
“…27, 43 The concept of ADE was initially proposed for dengue in 1977 and was supported by epidemiological observations in Cuba. 44,45 Data from Cuba demonstrated that DHF was more frequently observed in those patients who had evidence of previous infection with a different serotype. Recent work has provided further support for the concept of ADE.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 99%
“…When non-permissive human or monkey peripheral blood mononuclear cells are exposed to dengue virus in the presence of passively added anti-dengue antibody, viral replication takes place, provided that the antibody concentration is below the level that would neutralize the virus (Halstead & O'Rourke, 1977). These experiments provide the base upon which all subsequent dengue virus enhancement studies have been founded.…”
Section: Immunological Enhancement In Vitromentioning
confidence: 99%
“…Using dengue virus type 2, Halstead & O'Rourke (1977) demonstrated a dependence upon cellular Fc receptors, those on the human mononuclear cells they were using being trypsin resistant. They also showed that enhancement was mediated by antibodies of the IgG class, that IgM and F (ab')2 fragments were not able to enhance (although IgM showed weak activity in the presence of complement, Halstead, 1980b), and that the mammalian species in Which the antibodies were raised was immaterial (Halstead & O'Rourke, 1977). The trypsin sensitivity of the dengue virus receptors on human mononuclear cells has been further studied by Daughaday et al (1981).…”
Section: Mechanism Of Immunological Enhancement Of Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive singlestrand RNA genome (FIG. 3), which is approximately 11 kb in length, has a single open reading frame that encodes three structural proteins -the capsid (C), membrane (M) and envelope (E) glycoproteins -and seven non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5 [18][19][20] . ADE occurs when mononuclear phagocytes are infected through their Fc receptors by immune complexes that form between DENVs and non-neutralizing antibodies.…”
mentioning
confidence: 99%